Hydrologic characteristics of a drained tropical peat catchment : runoff coefficients, water table and flow duration curves - Katimon, Ayob; Abd. Wahab, Ahmad Khairi (Penerbit UTM Press, 2003)
Reclamation and drainage of peat basin is an important land development in Malaysia. A clear understanding on the hydrologic behavior of a drained peat basin is the essential factor towards an optimal management of the resource. Hydrological data from Madirono peat catchment located in Johor State, Malaysia was collected and used to characterise its hydrologic characteristics. The characterizations were made using the ordinary quantitative hydrologic approach. The magnitude of changes in the major hydrologic component of the study catchment was quantified. The study catchment experienced a large variation in runoff coefficient, indicating that a drained peat basin is a highly dynamic hydrologic system. A decaying trend in the annual runoff coefficient was observed. The annual runoff coefficients were large, ranging from 0.32 to 0.92. This indicates that the hydrology of the study catchment was extremely dynamics, highly permeable and very flashy. The low flow condition of the basin was extremely small but improving over time indicating that the basin could not sustain river flow during dry spell. The mean annual water table decreased over time by 2.7 cm per year.